Mortality and morbidity in relation to changes in albuminuria, glucose status and systolic blood pressure: an analysis of the ONTARGET and TRANSCEND studies - Schmieder, Roland; Schutte, Rudolph; Schumacher, Helmut; Boehm, Michael; Mancia, Giuseppe; Weber, Michael A.; Mcqueen, Matthew; Teo, Koon; Yusuf, Salim (Diabetologia, 2014)
Urinary albumin excretion is a strong predictor of cardiovascular disease. It is uncertain whether improvement from microalbuminuria or deterioration from normoalbuminuria over time in patients with differing changes in glucose and BP change their cardiovascular risk.Data on mortality, cardiovascular and renal outcomes were analysed in 22,984 patients from two large parallel randomised clinical trials followed for 56 months. A central laboratory analysed first morning spot urine samples at baseline and after 24 months, and events were recorded over the subsequent 32 months. Patients were stratified by changes in albuminuria, glucose status and mean systolic BP over 2 years.There was a strong association between albuminuria status and all-cause and cardiovascular mortality and combined cardiovascular and renal endpoints (all p < 0.0001). Changes in systolic BP control had no effect on mortality, whereas glucose status was significantly associated with all outcomes. Irrespective of BP control or glucose status, patients showing an improvement from microalbuminuria to normoalbuminuria after 2 years were at a lower risk of all outcome measures than patients showing deterioration from normoalbuminuria to microalbuminuria (HR for all-cause mortality 0.65 [0.52-0.83], p = 0.0004).Patients who showed improvement to normoalbuminuria over 2 years were at lower risk of all-cause and cardiovascular mortality and of cardiovascular and renal events than those who deteriorated to microalbuminuria over time. Albuminuria over time was significantly better than glucose status and BP control in predicting mortality and both cardiovascular and renal outcomes in patients at a high cardiovascular risk.
EVALuna2:3720